Radius-Maumenee Syndrome, A Rare Entity: A Case Report - Basnet, Rakshya; Singh, Sanjay Kumar (Nepalese Journal of Ophthalmology, 2023)
Background: Radius–Maumenee syndrome (RMS) is a rare idiopathic condition characterized by the enlargement of episcleral vessels and an elevation in intraocular pressure (IOP) leading to secondary glaucoma. Case: In this report, we present a case of RMS in 23-year-old male who experienced redness in Right Eye (RE) and intermittent headaches for a duration of 10 years. The patient exhibited a best corrected visual acuity of 6/6 in both eyes. Observations: During slit lamp biomicroscopy, episcleral venous engorgement was observed in both eyes. Tonometry measured 28 mmHg in the RE and 14 mmHg in Left Eye (LE). In fundus photographs of RE and LE, there was evident cup asymmetry, along with retinal nerve fiber layer defects in superotemporal and inferotemporal regions of the right eye. Optical coherence tomography (OCT) Optic Nerve Head with hood report of RE showed loss of double hump pattern with asymmetric and severe retinal nerve fiber layer thinning in superior and inferior quadrant. Visual field testing of RE showed superior and inferior arcuate scotoma. Brain and orbit magnetic resonance angiography (MRI Angiogram) revealed no abnormal voids indicating cavernous fistula or other orbital lesions. The presence of secondary open angle glaucoma with episcleral venous engorgement and negative test results for other potential conditions led to the diagnosis of RMS in the patient. The patient is now under combination therapy with aqueous suppressants and uveoscleral outflow increasing drugs. Conclusion: This case serves as a reminder to ophthalmologists about potential association of glaucoma if there’s enlargement of episcleral vessels in eyes without inflammation.